Algorithm for the distribution of the time-frequency resource in a cognitive radio network - Коляденко, Ю.Ю.; Муляр, Б.П. (Radiotekhnika, 2020)
The cognitive property implies the ability of a radio system to solve the following problems: transition from one standard to another; use of several standards; frequency tuning; the opportunity to participate in the dynamic distribution of the spectrum. One of the problems that arise when allocating a frequency resource may be the lack of clear decision rules. In such cases, as a rule, nonparametric algorithms and methods are used, such as, for example, algorithms based on the mathematical apparatus of neural networks, or algorithms built on the mathematical apparatus of fuzzy logic. An algorithm for the distribution of the time-frequency resource in the cognitive radio network is proposed. A distinctive feature of the developed algorithm is the use of both a parameter of the proportional fair distribution of physical resources PF and SINR. In addition, the decision in this algorithm is based on the mathematical apparatus of fuzzy logic. This algorithm can be used at the stage of network operation in the presence of a large number of speakers and centralized frequency management from the base station. A simulation model for managing the time-frequency resource is developed. A fuzzy inference system has been created for deciding on the allocation of a time-frequency resource. Input variables in this case are “requested resources” and “available resources”. The output variable is the "likelihood of resource provision." To form the “requested resources”, a fuzzy inference system has also been created. The input variables are “SINR” and “PF” (the ratio of the instantaneous data rate to the average throughput).